Diffraction theory as a tool for predicting airgap beneath a multi-column gravity based structure - Walker, D; Taylor, P; Taylor, R; Zang, J (2006)
This work investigates the feasibility of using diffraction solutions to predict extreme green water levels beneath multi-column gravity based structures. The ultimate aim is to provide improved design tools for predicting the height the deck structure must be raised above mean sea level (airgap) for the lower deck to avoid green water impact. Such tools, when fully validated, will replace the need to carry out model tests during preliminary design. Results for a real platform configuration are examined in this paper to highlight the key issues complicating the validation of diffraction based design tools for real structures. Incident regular waves are considered. Copyright ©2006 by The International Society of Offshore and Polar Engineers.